Antimicrobial Resistance Pattern of Escherichia Coli Isolated from Samples at Holy Family Hospital, Rawalpindi - Abdullah Nasir (Journal of Rawalpindi Medical College, 2018)
Background: Antibiotic resistance has become a major health problem worldwide in recent years and has increased morbidity and mortality as well as the cost of health care. Escherichia Coli in particular is a notorious microbe which causes multiple infections. We conducted this study to determine the antimicrobial resistance pattern, to commonly used antibiotics, of Escherichia coli obtained from various samples at Holy Family Hospital, Rawalpindi.